Psychometric properties of the Chinese version of the Trait Gratitude to Nature Scale - Li, Xiaoyu; Liang, Hongyu; Jin, Tonglin; Zhang, Jing; A, Yunna; Hu, Mulan; Wang, Yifan (Frontiers in Psychology, 2023)
The purpose of this study was to evaluate the reliability and validity of the Chinese version of the Trait Gratitude to Nature Scale (TGNS) for Chinese college students.: The original English version of the TGNS was translated into Chinese. Subsequently, two samples consisting of 1131 Chinese university students from Inner Mongolia Autonomous Region was recruited through online surveys to evaluate the psychometric properties of the Chinese version of the TGNS, including the discrimination, construct validity, criterion validity, reliability and gender invariance. Results: The Chinese version of the TGNS showed good psychometric properties. The item-total correlation coefficients of the scale ranged from 0.813 to 0.909. Exploratory factor analysis using data from Sample 1 (n = 617) demonstrated that the Chinese version of the TGNS has one factor. The confirmatory factor analysis using data from Sample 2 (n = 514) showed that the Chinese version of the TGNS has appropriate construct validity ( 2 /df = 4.157, RMSEA = 0.078, TLI = 0.943 and CFI = 0.967). The significant correlation between the Chinese version of the TGNS and all the other criterion scale scores (p < 0.001) indicated that the Chinese version of the TGNS displays good criterion validity. The test-retest reliability was 0.914, using the subsample of Sample 2 (n = 127). The results of gender invariance test indicated that the Chinese version of the TGNS has entire equivalence between the two genders.The Chinese version of the TGNS has satisfactory psychometric properties in the Chinese cultural context and can be used as s a reliable and valid instrument to assess trait gratitude to nature.